Mongolia : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2011)
To help economic adjustment in the midst of the global economic crisis, an 18-month Stand-By Arrangement (SBA) was supported by IMF resources. The cause of Mongolia's crisis in 2008-09 and its resolution and design and outcomes of the program are also discussed. The trigger for Mongolia's crisis was the collapse in the prices of its commodity exports-copper in particular. The program was concluded, having averted a full-blown crisis, and laid the foundation for further strengthening of the macroeconomic and financial policy framework.